Rotavirus and its Genotype Distribution among Children Less than Three Years Presenting with Acute Watery Diarrhoea to a General Hospital in Urban Nepal - Shrestha, Shrijana; Upadhyay, Bishwas; Limbu, Bhupendra; Pradhan, Rahul; Nakagomi, Tokoko; Thorson, Stephen; Pollard, Andrew J; Adhikari, Neelam (Journal of Nepal Paediatric Society, 2011)
Introduction: Viruses are the most common cause for diarrhoea in infants and small children. Rotavirus is the most frequent viral etiology, causing 125 million episodes of infantile diarrhoea and over 600,000 deaths per year. Materials and methods: A cross sectional study between January and March 2008 was conducted at Patan Hospital, Kathmandu to find out the prevalence of rotavirus among children < 3 years with watery diarrhoea and to identify common strains of rotavirus in the study population. Testing for rotavirus was undertaken by using Rota/Adeno screen Dipstick M583CE. Rotavirus strain identification was done at Nagasaki University Japan. Data was analyzed using SPSS® for Windows V 15.0 software. Results: 119 children with acute watery diarrhoea were enrolled. Rotavirus antigen was found in 63 cases (53%). The highest percentage of rotavirus infection was found in the second six months of life. Among the children with positive rotavirus antigen, the median age was 10 months (IRQ 8.00). The most predominant strain of rotavirus identified was G12 followed by G9 and G1. Most predominant G and P combination was G9 P[8] followed by G12P[6]. Conclusion: The study has shown the prevalence of unusual serotypes of rotavirus. Though rotavirus vaccine has been studied, used widely and found to be very effective, none of the vaccine efficacy studies have included common serotypes identified in Nepal. Level of protection conferred by infant immunization with the current rotavirus vaccines against the strains circulating in Nepal is unknown and careful surveillance through vaccine implementation is needed. Key words: Diarrhoea; Nepal; rotavirus; rotavirus genotypes; vaccine DOI: 10.3126/jnps.v31i2.4641 J Nep Paedtr Soc 2010;31(2):110-115